Closed die forging of powder preforms - Gupta A.K.; Jha A.K. (My University, 2025)
The present study is concerned with an upper bound solution constructed for determining the die load during completely closed die forging of metal powder preform under axi-symmetric condition. In the analysis, an appropriate interfacial friction law and yield criterion for porous material have been used. At the final stage of closed-die forging a product, the unfilled comers require huge working loads to fill them complete, and in some cases, this cannot be realized within the limits of the tool strength. The filling of comers in completely closed die forging of porous cylindrical shape is also considered for analysis. The results so obtained are analyzed and discussed to explain the interaction of various processing parameters involved and are presented graphically.